Pulmonary Allergic Responses Augment IL-13 Secretion by Circulating Basophils yet Suppress IFN-alpha from Plasmacytoid DCs - Schroeder, John T. (2010)
BACKGROUND: Allergic inflammatory processes may have the capacity to propagate systemically through the actions of circulating leukocytes. Consequently, basophils from allergic individuals are often “primed”, as evidenced by their hyper-responsiveness in vitro. IFN-α, secreted predominately by plasmacytoid DCs, suppresses basophil priming for IL-13 production in vitro. OBJECTIVE: This study sought in vivo correlates, arising during experimental allergen challenge, that support an “axis-interplay” between basophils and pDCs. METHODS: Using segmental allergen challenge in the lung, the immune responses of both cell types from blood were investigated in volunteers (n=10) before and 24h after allergen exposure. These responses were then correlated with inflammatory parameters measured in bronchoalveolar lavage fluids. RESULTS: In blood, segmental allergen challenge significantly augmented IL-13 secretion by basophils induced by IL-3 (p=0.009) yet reduced IFN-α secreted by plasmacytoid dendritic cells stimulated with CpG (p=0.018). Both parameters were negatively correlated (p=0.0015), at least among those subjects secreting the latter. Circulating basophil IL-13 responses further correlated with post-segmental allergen challenge bronchoalveolar lavage parameters including IL-13 protein (p=0.04), basophil (p=0.051), eosinophil (p=0.0018) and total cell counts (p<0.003). Basophil and IL-13 levels in bronchoalveolar lavage likewise correlated (p=0.0002). CONCLUSIONS: These results support a mechanism of immune regulation whereby allergen reduces innate immune responses and IFN-α production by plasmacytoid dendritic cells, resulting in enhanced inflammation and basophil cytokine production at sites of allergen exposure.